2006
DOI: 10.1158/1078-0432.ccr-06-1465
|View full text |Cite
|
Sign up to set email alerts
|

Grape Seed Extract Inhibits In vitro and In vivo Growth of Human Colorectal Carcinoma Cells

Abstract: Purpose: Accumulating evidences suggest the beneficial effects of fruit-and-vegetable consumption in lowering the risk of various cancers, including colorectal cancer. Herein, we investigated the in vitro and in vivo anticancer effects and associated mechanisms of grape seed extract (GSE), a rich source of proanthocyanidins, against colorectal cancer. Experimental Design: Effects of GSE were examined on human colorectal cancer HT29 and LoVo cells in culture for proliferation, cell cycle progression, and apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
116
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(129 citation statements)
references
References 43 publications
11
116
0
Order By: Relevance
“…We selected colorectal cancer as the first subject, because it has been the most common cancer type in Taiwan since 2007, when the dietary behavior of Taiwanese became more westernized [34] . Recent studies have revealed that the water reflux extract of longan flowers is enriched with two major compounds, (-)-epicatechin and proanthocyanidin A2 [26] , which are also found in grape seed extract as active anti-colorectal cancer agents [35,36] . Based on these reports, we proposed that LFE could play a possible role in colorectal cancer (CRC) prevention and treatment.…”
Section: Anti-colorectal Cancer Effects Of Lfementioning
confidence: 99%
See 2 more Smart Citations
“…We selected colorectal cancer as the first subject, because it has been the most common cancer type in Taiwan since 2007, when the dietary behavior of Taiwanese became more westernized [34] . Recent studies have revealed that the water reflux extract of longan flowers is enriched with two major compounds, (-)-epicatechin and proanthocyanidin A2 [26] , which are also found in grape seed extract as active anti-colorectal cancer agents [35,36] . Based on these reports, we proposed that LFE could play a possible role in colorectal cancer (CRC) prevention and treatment.…”
Section: Anti-colorectal Cancer Effects Of Lfementioning
confidence: 99%
“…The mechanisms of LFE in anti-CRC growth are mainly due to cell-cycle arrest in the S phase and induction of mitochondriamediated apoptosis. Previously, Kaur et al [36] reported that proanthocyanidin-rich grape seed extracts inhibited the proliferation of colorectal cancer cells due to their ability to cease G1-phase arrest of the cell cycle. However, LFE elevated cyclin E levels and downregulated cyclin A levels and arrested CRC cells in the DNA synthesis phase of the cell cycle.…”
Section: Anti-colorectal Cancer Effects Of Lfementioning
confidence: 99%
See 1 more Smart Citation
“…Condensed tannins are known as proanthocyanidins, which are the most abundant flavonoids present in GSE. 13 GSE demonstrated the strongest antioxidant effects and free radical scavenging ability 14 as well as being anti-inflammatory, 15 anticancer, 16 antibacterial 17 ; it has platelet aggregation inhibiting and metal chelating properties 18 and vasodilatory, immunostimulating, antiallergic, antiviral activates 19 ; it reduced plasma cholesterol in animals fed a high cholesterol diet and that may reduce risk of atherosclerosis. 20 Recently, GSE has been marketed as dietary supplement and advocated for its multiple beneficial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding mice with grape seed extract which is rich source of anthocyanidins at a dose of 200 mg/kg has been demonstrated to decrease colorectal tumor 44% in volume after 8 weeks of treatment and also induce apoptosis and cell cycle arrest of colon cancer. In addition, in rats fed with resveratrol orally at a dose of 60 mg/kg for 49 days, precancerous colonic lesions decreased [1][2][3][4].…”
Section: Introductionmentioning
confidence: 96%